Species identification of the Northern shrimp (Pandalus borealis) by polymerase chain reaction-restriction fragment length polymorphism and proteomic analysis - Pascoal, Ananías; Ortea, Ignacio; Gallardo, José Manuel; Cañas, Benito; Barros-Velázquez, Jorge; Calo-Mata, Pilar (Analytical Biochemistry, 2012)
12 páginas, 4 figuras, 2 tablas Genomic and proteomic techniques for species identification of meat and seafood products are being widely used. In this study, a genomic approach was used to differentiate Pandalus borealis (the Northern shrimp), which belongs to the superfamily Pandaloidea, from 30 crustaceans consisting of 19 commercially relevant prawns/shrimps species that belong to the superfamily Penaeoidea, which include the families Penaeidae and Solenoceridae, and 11 other crustacean species, including prawns, shrimps, lobsters, and crabs. For this purpose, a polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) method was designed based on the amplification of the 16S rRNA/tRNAVal/12S rRNA mitochondrial regions using the primers 16S-CruF and 16S-CruR. The 966-bp PCR products were produced and cleaved with the restriction enzymes AluI, TaqI, and HinfI, which provided species-specific restriction patterns. In addition, a proteomic approach, based on matrix-assisted laser desorption/ionization time-of-flight (MALDI–TOF) and electrospray ionization–ion trap (ESI–IT) mass spectrometry, was used to identify and characterize new P. borealis-specific peptides that could be useful as potential markers of this species in protein-based detection methods. To our knowledge, this is the first time a molecular method has been successfully applied to identify a wide range of prawn and shrimp species, including P. borealis, for either whole individuals or processed products. However, validation of the methods proposed here is required by applying them to a larger sample of individuals from different populations and geographic origins in order to avoid mainly false-negative results National Food Program of the INIA (Spanish Ministry for Education, project CAL-03-030-C2) and the PGIDIT Research Program in Marine Resources (project PGIDIT04RMA261004PR) of the Xunta de Galicia (Galician Council for Industry Commerce and Innovation) Peer reviewed